Hardness and elastic modulus of carbon-germanium alloys - Vilcarromero, J.; Marques, F. C. (Elsevier B.V., 2001)
This work reports on the mechanical properties of germanium-rich amorphous carbon-germanium alloys prepared by RF sputtering of a germanium/graphite target under an argon/hydrogen atmosphere. Nano-hardness, elastic modulus and stress were investigated as a function of the carbon content. The stress, which is reduced by the incorporation of carbon, was related to the film structure and to the difference in the Ge-Ge and Ge-C bond length. Contrary to what was expected, the hardness and elastic modulus of the alloys are lower than the corresponding values for pure amorphous hydrogenated germanium film, which in turn has both properties also smaller than those of crystalline germanium. These properties are analyzed in terms of the structural properties of the films. (C) 2001 Elsevier B.V. B.V All rights reserved.
Keywords: hardness; germanium-carbon; elastic modulus